Adaptive yoga versus low-impact exercise for adults with chronic acquired brain injury: a pilot randomized control trial protocol - Stephens, Jaclyn A.; Hernandez-Sarabia, Jesus A.; Sharp, Julia L.; Leach, Heather J.; Bell, Christopher; Thomas, Michael L.; Burzynska, Agnieszka; Weaver, Jennifer A.; Schmid, Arlene A. (Frontiers in Human Neuroscience, 2023)
Abstract Background: Each year, millions of Americans sustain acquired brain injuries (ABI) which result in functional impairments, such as poor balance and autonomic nervous system (ANS) dysfunction. Although significant time and energy are dedicated to reducing functional impairment in acute phase of ABI, many individuals with chronic ABI have residual impairments that increase fall risk, decrease quality of life, and increase mortality. In previous work, we have found that yoga can improve balance in adults with chronic (i.e., ≥ 6 months post-injury) ABI. Moreover, yoga has been shown to improve ANS and brain function in healthy adults. Thus, adults with chronic ABI may show similar outcomes. This protocol details the methods used to examine the effects of a group yoga program, as compared to a group low-impact exercise, on primary and secondary outcomes in adults with chronic ABI. Methods: This study is a single-blind randomized controlled trial comparing group yoga to group low-impact exercise. Participants must be ≥ 18 years old with chronic ABI and moderate balance impairments. Group yoga and group exercise sessions occur twice a week for one hour for eight weeks. Sessions are led by trained adaptive exercise specialists. Primary outcomes are balance and ANS function. Secondary outcomes are brain function and structure, cognition, quality of life, and qualitative experiences. Data analysis for primary and most secondary outcomes will be completed with mixed effect statistical methods to evaluate the within-subject factor of time (i.e., pre vs. post intervention), the between-subject factor of group (yoga vs. low-impact exercise), and interaction effects. Deductive and inductive techniques will be used to analyze qualitative data. Discussion: Due to its accessibility and holistic nature, yoga has significant potential for improving balance and ANS function, along with other capacities, in adults with chronic ABI. Because there are also known benefits of exercise and group interaction, this study compares yoga to a similar, group exercise intervention to explore if yoga has a unique benefit for adults with chronic ABI. Trial registration: ClinicalTrials.gov, NCT05793827. Registered on March 31, 2023.